PERSEPSI MAHASISWA AKUNTANSI TERHADAP ETIKA PENDIDIK PADA PROGRAM STUDI AKUNTANSI UNIVERSITAS MUHAMMADIYAH PONOROGO - Nurul Hidayah (Ekuilibrium: Jurnal Ilmiah Bidan Ilmu Ekonomi, 2016)
This study aims to determine the suitability of the behavior of Accountants educators at the Faculty of Economics, University of Muhammadiyah Ponorogo with IAI code of ethics and code of conduct set forth in University of Muhammadiyah Ponorogo. Total population of 528 students with sample criteria S1 students are active in 6th semester and have taken the course of business ethics. Its a Quantitative Descrpitive Research. Collecting data using questionnaires and interviews. The samples used as many as 90 students. Results of research by 56.27% of the students answered agree, which means according to student perception, that the accountant educators at the Faculty of Economics, University of Muhammadiyah Ponorogo has implemented a code of ethics accountant with good educators in their duties. A total of 84.3% ofaccountants educator has implemented a code of ethics and 15.7% are still there accountant educators who behave unethically.